2011
DOI: 10.1371/journal.pone.0020600
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA and Target Protein Patterns Reveal Physiopathological Features of Glioma Subtypes

Abstract: Gliomas such as oligodendrogliomas (ODG) and glioblastomas (GBM) are brain tumours with different clinical outcomes. Histology-based classification of these tumour types is often difficult. Therefore the first aim of this study was to gain microRNA data that can be used as reliable signatures of oligodendrogliomas and glioblastomas. We investigated the levels of 282 microRNAs using membrane-array hybridisation and real-time PCR in ODG, GBM and control brain tissues. In comparison to these control tissues, 26 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
94
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(101 citation statements)
references
References 66 publications
3
94
0
4
Order By: Relevance
“…Recently, miR-134 has been implicated in the pathogenesis of several types of tumors and plays dual roles in different tumors. It is significantly increased in head and neck squamous-cell carcinoma (HNSCC) and acts as a potential oncogene (Liu et al, 2014), while it is downregulated and acts as a candidate tumor suppressor in gastrointestinal stromal tumors (GISTs) (Haller et al, 2010), gliomas (Lages et al, 2011), non-small cell lung cancer (Li et al, 2012), hepatocellular carcinoma (Yin et al, 2013), and prostate cancer (Wang et al, 2011). However, very little is currently known about the links of miR-134 dysregulation to clinicopathological characteristics of osteosarcoma, and the functional attributes of miR-134 associated with osteosarcoma progression remain elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, miR-134 has been implicated in the pathogenesis of several types of tumors and plays dual roles in different tumors. It is significantly increased in head and neck squamous-cell carcinoma (HNSCC) and acts as a potential oncogene (Liu et al, 2014), while it is downregulated and acts as a candidate tumor suppressor in gastrointestinal stromal tumors (GISTs) (Haller et al, 2010), gliomas (Lages et al, 2011), non-small cell lung cancer (Li et al, 2012), hepatocellular carcinoma (Yin et al, 2013), and prostate cancer (Wang et al, 2011). However, very little is currently known about the links of miR-134 dysregulation to clinicopathological characteristics of osteosarcoma, and the functional attributes of miR-134 associated with osteosarcoma progression remain elusive.…”
Section: Introductionmentioning
confidence: 99%
“…microRNA-21 shows overexpression in GBM and other gliomas in a grade-specific manner [4,7,31,34,41,59]. It affects the major cancer pathways: TGF-β, p53, and mitochondrial initiated apoptosis pathways.…”
Section: Candidate Micrornas For High-grade Gliomas Biomarkersmentioning
confidence: 99%
“…A number of miRNA has been reported to be overexperessed in GBM (Conti et al, 2009). In a recent report, it has been found that seven miRNAs expression pattern (miR-21, miR-128, miR-132, miR-134, miR-155, miR-210 and miR-409) allows to discriminate between oligodendroglioma and glioblastoma (Conti et al, 2009;Ciafre et al, 2005;Lages et al, 2011). They are thought to play very important role in cell cycle control, cell proliferation, differentiation and apoptosis (EsquelaKerscher et al, 2006).…”
Section: Micro Rna and Gliomasmentioning
confidence: 99%